Anterior pituitary influence on adipokine expression and secretion by porcine adipocytes - R. Saleri; V. Cavalli; P. Martelli; P. Borghetti (Animal, 2016)
Nutritional stressors may cause negative effects on animal health and growth and lead to significant economic impact. Adipose tissue is an endocrine organ producing, mediators and hormones, called adipokines. They play a dynamic role in body homeostasis and in the regulation of energy expenditure, interacting with feeding behavior, hormones and growth factors. This in vitro study aimed to investigate how nutritional conditions and growth hormone (GH) can influence nitric oxide (NO) production and the expression and secretion of three important adipokines, that is leptin, interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α), by swine adipocytes. In our experimental model, mesenchymal stem cells from omental adipose tissue were induced to adipogenic differentiation. After differentiation, adipocytes were incubated for 24 h (T0) with DMEM/Ham’s F12 (group A) or DMEM/Ham’s F12 salts (group B), a DMEM/Ham’s F12 formulation deprived of nutritional components. Primary adipocyte cells were also co-cultured for 4 h (T+4) or 12 h (T+12) with or without anterior pituitary slices. To stimulate GH secretion by pituitary cells, growth hormone releasing hormone at 10−8 M was added at the start of the incubation times (4 or 12 h). At T0, T+4 and T+12, NO production, leptin, IL-6 and TNF-α expression and secretion were measured. NO increased (P<0.05) up to twofold in restricted culture conditions. Deprived medium and coincubation with anterior pituitary positively influenced leptin secretion and expression. TNF-α was expressed and secreted only in deprived culture condition groups (B, B1 and B2). Nutrients availability and pituitary co-culture did not affect IL-6 expression and secretion. Our study shows an endocrine function for porcine adipocytes. In our model, adipocytes readily responded to nutritional inputs by secretion of molecules affecting energy balance. This secretion capacity was modulated by GH. Improving our knowledge of the role of adipocyte in the endocrine system, may lead to a more complete understanding of regulating energy balance in swine.